Sodium ferrous fluorophosphate positive electrode material for sodium ion battery and preparation method of sodium ferrous fluorophosphate positive electrode material

By improving the raw material ratio and process flow, the sodium ferrous phosphate positive electrode material is prepared by ball milling and phased heating sintering, which solves the problems of low energy density and poor cycle stability in the existing technology, and achieves high efficiency and low cost Preparation of sodium ion battery positive electrode material, suitable for large-scale production.

CN119218959APending Publication Date: 2024-12-31JIANGXI JINLI TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411388825.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode materials have low energy density, poor cycle stability, complex preparation process and high cost, making it difficult to meet the needs of industrial production.

Method used

Using sodium bicarbonate, iron phosphate, sodium fluoride and glucose as raw materials, ball milling in a low boiling point solvent, and then heating and sintering in stages under a nitrogen atmosphere to prepare a high-purity sodium ferrous fluorine phosphate positive electrode material, simplifying the process flow and Reduce energy consumption.

Benefits of technology

It improves the electrochemical performance of the material, especially in terms of discharge capacity and cycle stability, reduces production costs, and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119218959A_ABST
    Figure CN119218959A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of new energy storage, and discloses a sodium ferrous fluorophosphate positive electrode material for a sodium ion battery and a preparation method thereof.The preparation method comprises the steps that a sodium-containing compound, sodium fluoride, iron phosphate and a proper carbon source serve as raw materials and are added into a low-boiling-point solvent, and raw material monomers are evenly dispersed in the solvent through a simple ball milling technology; putting the ball-milled material mixed solution into a drying oven to be dried and volatilized until no solvent is left, so as to obtain a precursor of the sodium ferrous fluorophosphate positive electrode material; and sintering, grinding and sieving the obtained precursor material to obtain a final product. The preparation method is simple and convenient to operate, relatively low in energy consumption and easy to realize large-scale production, the comprehensive performance of the sodium ion battery is effectively improved, and the commercial application process of the sodium ion battery is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of new energy storage, and in particular relates to a sodium ferrous fluorophosphate positive electrode material for a sodium ion battery and a preparation method thereof. Background Art

[0002] The rapid development of the new energy industry has put forward higher and higher requirements for energy storage technology. As a potential energy storage technology, sodium-ion batteries have gradually become a hot topic of research due to their abundant resources and low cost. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. Sodium ions migrate between the positive and negative electrodes to achieve charging and discharging. However, the larger radius of sodium ions limits the energy density and cycle life of the battery. The traditional positive electrode materials of sodium-ion batteries have low capacity and poor cycle stability, which limits their commercial application. At present, the positive electrode materials of sodium-ion batteries mainly include layered oxides, polyanion compounds and Prussian blue compounds. Layered oxides have high theoretical capacity, but their structure is unstable, resulting in rapid capacity decay; Prussian blue compounds are low in cost and easy to prepare, but have low energy density. In contrast, phosphate-based polyanion compounds such as sodium ferrous fluorophosphate have gradually become the focus of research due to their stable olivine structure and excellent electrochemical properties.

[0003] Sodium ferrous fluorophosphate is a polyanionic compound with an olivine structure. Sodium ions and iron ions occupy specific lattice positions respectively, while phosphate and fluoride ions are connected to them through chemical bonds to form a stable lattice. This structure not only provides a higher theoretical capacity, but also ensures the rapid migration of sodium ions and improves the electrochemical performance of the material. In addition, the introduction of fluoride ions enhances the structural stability of the material, helps to maintain the integrity of the lattice and prolong the battery cycle life. However, the existing preparation process has shortcomings. Although the solid phase method is commonly used, it is difficult to ensure uniform mixing of raw materials, and the grains are easy to grow during high-temperature sintering, which affects the electrochemical performance, and the reaction time is long and the energy consumption is high, which is not conducive to large-scale production. Liquid phase precipitation method and sol-gel method can synthesize more uniform sodium ferrous fluorophosphate at a lower temperature, but the reaction conditions are high and the recovery and treatment are complicated, resulting in increased production costs, difficult to control product purity, and difficult to meet the needs of industrial production.

[0004] In view of the shortcomings of the prior art, it is urgent to develop a simple, efficient and low-cost method for preparing sodium ferrous fluorophosphate positive electrode materials, which can reduce production energy consumption and improve the purity and consistency of materials while maintaining high electrochemical performance. The present invention aims at the defects in the existing preparation methods and proposes an optimized sodium ferrous fluorophosphate preparation process. By improving the raw material ratio and process flow, the electrochemical performance of the material can be effectively improved, and the production cost can be significantly reduced, which is suitable for large-scale production.

[0005] The present invention successfully prepares a sodium ferrous fluorophosphate positive electrode material with excellent performance through reasonable process optimization and raw material selection, overcomes the shortcomings of the prior art, promotes the development of sodium ion battery positive electrode materials, and has important innovation, practicality and application value. Summary of the invention

[0006] The present invention relates to a sodium ferrous fluorophosphate positive electrode material for a sodium ion battery and a preparation method thereof. By using sodium bicarbonate, ferric phosphate, sodium fluoride and glucose as raw materials, ball milling is performed in a low boiling point solvent to obtain a uniform precursor material. Subsequently, the temperature is raised and sintered in stages under a nitrogen atmosphere to synthesize a high-purity sodium ferrous fluorophosphate material at a relatively low temperature. The method simplifies the process flow, reduces energy consumption and production costs, and improves the electrochemical properties of the material, especially in terms of discharge capacity, cycle stability and rate performance, and meets the requirements of sodium ion batteries for positive electrode materials.

[0007] A sodium ferrous fluorophosphate positive electrode material for a sodium ion battery and a preparation method thereof, comprising the following steps: S1: Raw material ratio: the raw material ratio is carried out according to the ratio of sodium source, iron source, phosphorus source and carbon source, specifically including sodium bicarbonate as sodium source, ferric phosphate as phosphorus source and iron source, sodium fluoride as sodium source and fluorine source, glucose as carbon source, and the ingredients are prepared according to the molar ratio of the four elements of Na, F, Fe and P in the range of 1.5~2.5:0.8~1.2:0.8~1.2:0.8~1.2; Preferably, the molar ratio of the four elements Na, F, Fe, and P is 1.7~2.2:0.9~1.1:0.9~1.1:0.9~1.1; S2: Solution preparation: dissolving the raw materials in anhydrous ethanol and stirring evenly with a stirrer to form a suspension A; S3: ball milling: transferring the suspension A to a ball mill for mixing and refining to improve the uniformity and reactivity of the material and form a uniform suspension B; S4: Drying treatment: transferring the ball-milled suspension B to an oven for drying, evaporating the ethanol in the solution, and obtaining a solid precursor of the sodium ferrous fluorophosphate positive electrode material; S5: Sintering process: The precursor is heated in stages under a nitrogen atmosphere, firstly heated to 320-380°C at a rate of 4-6°C / min and kept warm for 2-4 hours, then heated to 580-620°C at the same heating rate and kept warm for 6-10 hours, and finally sodium ferrous fluorophosphate positive electrode material is obtained; Preferably, the temperature is increased to 320, 350 or 380°C at a heating rate of 4°C / min, 5°C / min or 6°C / min, and kept at this temperature for 2 hours, 3 hours or 4 hours; S6: Screening: After grinding the sintered sodium ferrous fluorophosphate positive electrode material, screen it using a 150-300 mesh screen to ensure uniform material particles; Preferably, the mesh size of the sieve is 150 mesh, 250 mesh or 300 mesh.

[0008] In some of the embodiments, the ball milling process has a rotation speed ranging from 400 to 500 rpm, and a ball milling time ranging from 4 to 8 hours.

[0009] Preferably, the ball milling speed is 400 rpm, 450 rpm or 500 rpm, and the time is 4 hours, 5 hours or 8 hours.

[0010] In some embodiments, the drying temperature of the precursor is in the range of 80-100° C. and the drying time is in the range of 8-12 hours.

[0011] Preferably, the drying temperature is 80°C, 90°C or 100°C.

[0012] In some embodiments, in step S2, the agitator speed is set to 300-600 rpm, and the stirring time is 5-10 minutes.

[0013] Preferably, the stirrer speed is 300 rpm, 400 rpm or 600 rpm.

[0014] In some of the embodiments, the obtained sodium ferrous fluorophosphate positive electrode material is carbon-coated.

[0015] In some embodiments, the solid content of the suspension is in the range of 30% to 40%.

[0016] Preferably, the solid content of the suspension is 30%, 35% or 40%.

[0017] In some of the embodiments, in the step S6, the grinding time is 1 to 5 hours, the speed is 200 to 600 rpm, the ball diameter is 1 to 10 mm, and the mass ratio of the grinding medium to the material is 10:1 to 30:1.

[0018] Preferably, the grinding time is 1 hour, 3 hours or 5 hours, the speed is 200 rpm, 400 rpm or 600 rpm, the ball diameter is 1 mm, 5 mm or 10 mm, and the mass ratio is 10:1, 20:1 or 30:1.

[0019] In some of the embodiments, the purity of sodium fluoride used in the material preparation process is 99% to 99.5%, which ensures the stability of fluoride ions and improves the cycle performance of sodium ion batteries.

[0020] Preferably, the purity of sodium fluoride is 99%, 99.3% or 99.5%.

[0021] In some of the embodiments, the purity of nitrogen during the sintering process is above 99.9%, and the flow rate is 20-100 mL / min, ensuring the purity of the reaction environment.

[0022] Preferably, the flow rate is 20 mL / min, 50 mL / min or 100 mL / min.

[0023] (1) Simplify the preparation process. The preparation method of the present invention is easy to operate and can be easily scaled up for production, which is beneficial to promoting the commercialization of sodium ion batteries.

[0024] (2) The reaction temperature of the present invention is relatively mild, the preparation process is efficient and the energy consumption is low, and the prepared positive electrode material has a high discharge capacity and good cycle performance. In addition, by controlling the reaction means, the purity of the synthesized material is relatively high. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a preparation flow chart of the sodium ferrous fluorophosphate positive electrode material involved in the present invention. DETAILED DESCRIPTION

[0026] In order to facilitate the understanding of the technical implementation method of the present invention, the technical scheme in the embodiment of the present invention will be clearly and completely described below in combination with the technical process steps, specific implementation conditions and materials in the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example

[0027] The preparation method of sodium ferrous fluorophosphate positive electrode material comprises the following specific steps: Sodium bicarbonate was used as the sodium source, ferric phosphate as the phosphorus source and iron source, sodium fluoride as the supplementary sodium source and fluorine source, and glucose as the carbon source, and the ingredients were prepared according to the ratio of Na, F, Fe, and P of 2:1:1:1. 60g of the reaction raw materials were weighed, dissolved in 100L of anhydrous ethanol, and stirred to form a suspension A with a solid content of 38%. Subsequently, suspension A was transferred to a ball mill and ball milled at 450rpm for 6 hours to obtain suspension B. Then, suspension B was transferred to an oven and dried at 90°C for 10 hours to obtain a precursor. Finally, the precursor was heated to 350°C at a heating rate of 5°C / min under a nitrogen atmosphere and kept warm for 3 hours, and then heated to 600°C at a heating rate of 5°C / min and kept warm for 8 hours, and finally 53g of carbon-coated sodium ferrous fluorophosphate positive electrode material was obtained. Example

[0028] The preparation method of sodium ferrous fluorophosphate positive electrode material is as follows: Sodium bicarbonate was used as the sodium source, ferric phosphate as the phosphorus source and iron source, sodium fluoride as the supplementary sodium source and fluorine source, and glucose as the carbon source. The ingredients were prepared according to the ratio of Na, F, Fe, and P of 2.2:1:1:1. Weigh 50g of the reaction raw materials, dissolve the raw materials in 90L of anhydrous ethanol, and stir to form a suspension A with a solid content of 35%. Subsequently, the suspension A was transferred to a ball mill and ball milled at 420rpm for 8h to obtain a suspension B. Then, the suspension B was transferred to an oven and dried at 85℃ for 8h to obtain a precursor. Finally, the precursor was heated to 330℃ at 4℃ / min under a nitrogen atmosphere for 2h; then heated to 590℃ at 5℃ / min for 7h, and finally 45g of carbon-coated sodium ferrous fluorophosphate positive electrode material was obtained. Example

[0029] The preparation method of sodium ferrous fluorophosphate positive electrode material is as follows: Sodium bicarbonate was used as the sodium source, ferric phosphate as the phosphorus source and iron source, sodium fluoride as the sodium source and fluorine source, and glucose as the carbon source, and the ingredients were prepared according to the ratio of Na, F, Fe, and P of 1.7:0.9:0.9:0.9. Weigh 70g of the reaction raw materials, dissolve the raw materials in 110L of anhydrous ethanol, and stir to obtain suspension A with a solid content of 40%. Subsequently, suspension A was transferred to a ball mill, and suspension B was obtained after ball milling at a speed of 460rpm for 5h. Next, suspension B was transferred to an oven and dried at 95℃ for 12h to obtain a precursor. Finally, the precursor was heated to 360℃ at 5℃ / min under a nitrogen atmosphere for 3.5h; then heated to 610℃ at 5℃ / min for 9h, and finally 58g of carbon-coated sodium ferrous fluorophosphate positive electrode material was obtained. Example

[0030] The preparation method of sodium ferrous fluorophosphate positive electrode material is as follows: Sodium bicarbonate was used as the sodium source, ferric phosphate as the phosphorus and iron sources, sodium fluoride as the sodium and fluorine sources, and glucose as the carbon source, and the ingredients were prepared according to the ratio of Na, F, Fe, and P of 2:1:1:0.9. Weigh 55g of the reaction raw materials, dissolve the raw materials in 95L of anhydrous ethanol, and stir to obtain suspension A with a solid content of 37%. Subsequently. Suspension A was transferred to a ball mill, and suspension B was obtained after ball milling at a speed of 440rpm for 7h. Then, suspension B was transferred to an oven and dried at 80℃ for 9h to obtain a precursor. Finally, the precursor was heated to 345℃ at 4.5℃ / min under a nitrogen atmosphere for 4h; then heated to 595℃ at 4.5℃ / min for 8h, and finally 50g of carbon-coated sodium ferrous fluorophosphate positive electrode material was obtained. Example

[0031] The preparation method of sodium ferrous fluorophosphate positive electrode material is as follows: Sodium bicarbonate was used as the sodium source, ferric phosphate as the phosphorus and iron sources, sodium fluoride as the sodium and fluorine sources, and glucose as the carbon source, and the ingredients were prepared according to the ratio of Na, F, Fe, and P of 2:0.9:1.1:1. Weigh 65g of the reaction raw materials, dissolve the raw materials in 105L of anhydrous ethanol, and stir to obtain suspension A with a solid content of 30%. Subsequently, suspension A was transferred to a ball mill, and suspension B was obtained after ball milling at a speed of 430rpm for 6h. Next, suspension B was transferred to an oven and dried at 92℃ for 10h to obtain a precursor. Finally, the precursor was heated to 355℃ at 5℃ / min and kept warm for 3h under a nitrogen atmosphere; then heated to 605℃ at 5℃ / min and kept warm for 8.5h, and finally 57g of carbon-coated sodium ferrous fluorophosphate positive electrode material was obtained. Example

[0032] The preparation method of sodium ferrous fluorophosphate positive electrode material is as follows: Sodium bicarbonate was used as the sodium source, ferric phosphate as the phosphorus and iron sources, sodium fluoride as the sodium and fluorine sources, and glucose as the carbon source, and the ingredients were prepared according to the ratio of Na, F, Fe, and P of 2.1:1:0.9:1. Weigh 58g of the reaction raw materials, dissolve the raw materials in 98L of anhydrous ethanol, and stir to obtain suspension A with a solid content of 33%. Subsequently, suspension A was transferred to a ball mill, and suspension B was obtained after ball milling at 440rpm for 7h. Next, suspension B was transferred to an oven and dried at 100℃ for 10h to obtain a precursor. Finally, the precursor was heated to 340℃ at 4.5℃ / min and kept warm for 3.5h under a nitrogen atmosphere; then heated to 600℃ at 5℃ / min and kept warm for 9h, and finally 52g of carbon-coated sodium ferrous fluorophosphate positive electrode material was obtained.

[0033] Example 7: Performance Test In order to test the electrochemical performance of the sodium ferrous fluorophosphate positive electrode material prepared by the present invention, the following method was used: Electrode preparation: The sodium ferrous fluorophosphate positive electrode materials prepared in Example 1, Example 2 and Example 3 were mixed with conductive carbon black and polyvinylidene fluoride (PVDF) at a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone (NMP) was added to prepare a slurry. The slurry was evenly coated on aluminum foil, vacuum dried for 12 hours, and then cut into electrode sheets with a diameter of 12 mm for standby use.

[0034] Battery assembly: The prepared cathode material sheet, electrolyte (1 M NaClO4 dissolved in a 1:1:1 mixed solvent of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate with 5% fluoroethylene carbonate added) and sodium metal sheet as the counter electrode were assembled into a CR2032 button cell.

[0035] Electrochemical testing: Cyclic voltammetry (CV): CV tests were performed using a CHI660E electrochemical workstation with the voltage range set at 2.0 V to 4.0 V and a scan rate of 0.1 mV / s to record the redox behavior of the material.

[0036] Battery charge and discharge performance test: The button cell was subjected to constant current charge and discharge test on the Neware battery test system, with a current density of 0.1 C and a voltage range of 2.0 V ~ 4.5 V, to test the first discharge specific capacity and cycle performance of the material.

[0037] Test results: Example 1 The prepared positive electrode material has an initial discharge specific capacity of 115 mAh / g, and a capacity retention rate of 92% after 100 cycles, which shows excellent cycle stability.

[0038] Example 2 The first discharge specific capacity of the prepared positive electrode material is 110 mAh / g, and the capacity retention rate after 100 cycles is 89%.

[0039] Example 3 The first discharge specific capacity of the prepared positive electrode material is 110 mAh / g, but the capacity retention rate after 100 cycles is 88%.

[0040] Example 4 The first discharge specific capacity of the prepared positive electrode material is 108 mAh / g, but the capacity retention rate after 100 cycles is 85%.

[0041] Example 5 The first discharge specific capacity of the prepared positive electrode material is 107 mAh / g, but the capacity retention rate after 100 cycles is 84%.

[0042] Example 6 The first discharge specific capacity of the prepared positive electrode material is 107 mAh / g, but the capacity retention rate after 100 cycles is 80%.

[0043] Performance summary: By comparing the electrochemical performance test results of Examples 1 to 6, the sodium ferrous fluorophosphate positive electrode material in Example 1 exhibits the most excellent electrochemical performance, with a higher initial discharge specific capacity and good cycle stability. In particular, the capacity retention rate after 100 cycles reaches 92%, showing strong long-term stability, and is suitable for practical applications in sodium ion batteries.

[0044] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A sodium ferrous fluorophosphate positive electrode material for sodium ion battery and a preparation method thereof, characterized in that: The following steps are involved: S1: Raw material ratio: the raw material ratio is carried out according to the ratio of sodium source, iron source, phosphorus source and carbon source, specifically including sodium bicarbonate as sodium source, ferric phosphate as phosphorus source and iron source, sodium fluoride as sodium source and fluorine source, glucose as carbon source, and the ingredients are prepared according to the molar ratio of the four elements of Na, F, Fe and P in the range of 1.5~2.5:0.8~1.2:0.8~1.2:0.8~1.2; S2: Solution preparation: dissolving the raw materials in anhydrous ethanol and stirring evenly with a stirrer to form a suspension A; S3: ball milling: transferring the suspension A to a ball mill for mixing and refining to improve the uniformity and reactivity of the material and form a uniform suspension B; S4: Drying treatment: transferring the ball-milled suspension B to an oven for drying, evaporating the ethanol in the solution, and obtaining a solid precursor of the sodium ferrous fluorophosphate positive electrode material; S5: Sintering process: The precursor is heated in stages under a nitrogen atmosphere, firstly heated to 320-380°C at a rate of 4-6°C / min and kept warm for 2-4 hours, then heated to 580-620°C at the same heating rate and kept warm for 6-10 hours, and finally sodium ferrous fluorophosphate positive electrode material is obtained; S6: Screening: After grinding the sintered sodium ferrous fluorophosphate positive electrode material, use a 150-300 mesh screen to screen it to ensure uniform material particles.

2. The sodium ferrous fluorophosphate positive electrode material for sodium ion battery and the preparation method thereof according to claim 1, characterized in that: The rotation speed range of the ball milling process is 400-500 rpm, and the ball milling time is 4-8 hours.

3. The sodium ferrous fluorophosphate positive electrode material for sodium ion battery and the preparation method thereof according to claim 1, characterized in that: The drying temperature of the precursor is in the range of 80-100° C. and the drying time is 8-12 hours.

4. The sodium ferrous fluorophosphate positive electrode material for sodium ion battery and the preparation method thereof according to claim 1, characterized in that: In the step S2, the stirring speed is set to 300-600 rpm, and the stirring time is 5-10 minutes.

5. The sodium ferrous fluorophosphate positive electrode material for sodium ion battery and the preparation method thereof according to claim 1, characterized in that: The obtained sodium ferrous fluorophosphate positive electrode material is a carbon-coated type.

6. The sodium ferrous fluorophosphate positive electrode material for sodium ion battery and the preparation method thereof according to claim 1, characterized in that: The solid content of the suspension is in the range of 30% to 40%.

7. The sodium ferrous fluorophosphate positive electrode material for sodium ion battery and the preparation method thereof according to claim 1, characterized in that: In the step S6, the grinding time is 1 to 5 hours, the speed is 200 to 600 rpm, the ball diameter is 1 to 10 mm, and the mass ratio of the grinding medium to the material is 10:1 to 30:

1.

8. The sodium ferrous fluorophosphate positive electrode material for sodium ion battery and the preparation method thereof according to claim 1, characterized in that: The purity of sodium fluoride used in the material preparation process is 99% to 99.5%, which ensures the stability of fluoride ions and improves the cycle performance of sodium ion batteries.

9. The sodium ferrous fluorophosphate positive electrode material for sodium ion battery and the preparation method thereof according to claim 1, characterized in that: The purity of nitrogen during the sintering process is above 99.9%, and the flow rate is 20-100 mL / min, ensuring the purity of the reaction environment.